2005
DOI: 10.1055/s-2004-830388
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Subaortic Stenosis: Long-Term Prognosis on the Progression of the Obstruction and of the Aortic Insufficiency

Abstract: DSS is a variable, unpredictable and progressive disease; recurrent obstruction may reappear despite the adequacy of surgical excision, and is not related to preoperative gradient. Mild AI remains substantially unchanged and AVR is indicated in severe AI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 11 publications
1
20
2
1
Order By: Relevance
“…Our reoperation rate for recurrent DSS (1.8% per patient-year) was comparable to that in 2 other adult surgical series, which reported reoperation rates of 0.5% and 2.6% per patient-year. 15,27 As reported in several studies in children with DSS, a higher peak instantaneous gradient across the LVOT at the final preoperative echocardiogram was an independent predictor for reoperation in our adult patient population. 10,12,16,17,24 Testing various cutoff points, we found that a peak instantaneous LVOT gradient ≥80 mm Hg is most predictive of the need of reoperation.…”
Section: Dss Recurrence and Reoperationssupporting
confidence: 49%
See 1 more Smart Citation
“…Our reoperation rate for recurrent DSS (1.8% per patient-year) was comparable to that in 2 other adult surgical series, which reported reoperation rates of 0.5% and 2.6% per patient-year. 15,27 As reported in several studies in children with DSS, a higher peak instantaneous gradient across the LVOT at the final preoperative echocardiogram was an independent predictor for reoperation in our adult patient population. 10,12,16,17,24 Testing various cutoff points, we found that a peak instantaneous LVOT gradient ≥80 mm Hg is most predictive of the need of reoperation.…”
Section: Dss Recurrence and Reoperationssupporting
confidence: 49%
“…15,27,28 Therefore, the aim of this study was to identify risk factors for postoperative DSS recurrence, AR progression, and reoperation in a large cohort of adult patients who previously underwent surgical treatment for DSS.…”
Section: Clinical Perspective On P 1191mentioning
confidence: 99%
“…van der Linde et al 2 joins those by Oliver et al, 15 Stassano et al, 16 and Vogt et al 17 on patients followed up into early adulthood and, for a few, beyond. The group studied by Vogt et al 17 contains a number of more severe and lengthy LVOT lesions, which makes comparisons with DSS patients difficult.…”
Section: Foker Discrete Subaortic Stenosis 1449mentioning
confidence: 84%
“…For these series, the gradient increased at an average rate of ≈1 to 3 mm Hg per year, although with considerable variation. 2,15,16 The results of the first resection appeared to be equally effective whatever the initial gradient, but as might be expected, the rate of increase was greater in patients with more obstruction initially, which suggests a more difficult LVOT. Somewhat surprisingly, the gradient also increased more quickly in females and older patients.…”
Section: Foker Discrete Subaortic Stenosis 1449mentioning
confidence: 84%
See 1 more Smart Citation